Numerical Simulation and Analysis of Micropile-Raft Joint Jacking Technology for Rectifying Inclined Buildings Due to Uneven Settlement - Ming Xie; Li’e Yin; Zhangdong Wang; Fangbo Xu; Xiangdong Wu; Mengqi Xu (Buildings)
To address the issue of structural tilting caused by uneven foundation settlement in soft soil areas, this study combined a specific engineering case to conduct numerical simulations of the rectification process for an inclined reinforced concrete building using ABAQUS finite element software. Micropile-raft combined jacking technology was employed, applying staged jacking forces (2400 kN for Axis A, 2200 kN for Axis B, and 1700 kN for Axis C) with precise control through 20 incremental steps. The results demonstrate that this technology effectively halted structural tilting, reducing the maximum inclination rate from 0.51% to 0.05%, significantly below the standard limit. Post-rectification, the peak structural stress decreased by 42%, and displacements were markedly reduced. However, the jacking process led to a notable increase in the column axial forces and directional changes in beam bending moments, reflecting the dynamic redistribution of internal forces. The study confirms that micropile-raft combined jacking technology offers both controllability and safety, while optimized counterforce pile layouts enhance the long-term stability of the rectification system. Based on stress and displacement cloud analysis, a monitoring scheme is proposed, forming an integrated “rectification-monitoring-reinforcement” solution, which provides a technical framework for building rectification in soft soil regions.